Oncotype DX® in breast cancer patients: clinical experience, outcome and follow-up : a case : control study - Rath, Michèlle Geneviève; Uhlmann, Lorenz; Heil, Jörg; Golatta, Michael; Dinkic, Christine; Hennigs, André; Schott, Sarah; Sohn, Christof; Rom, Joachim (Archives of gynecology and obstetrics, 2018)
PurposeBreast cancer is the leading cause of death from cancer in women and the most common cancer in the world [1]. To date, many patients with estrogen-receptor-positive (ER+) breast cancer are overtreated with chemotherapy when the rationale for adjuvant chemotherapy is based on clinicopathologic parameters. Different studies were able to demonstrate that a 21-gene expression assay (Oncotype DX® Genomic Health, Redwood City, CA) can predict the benefit from adjuvant chemotherapy in ER+ breast cancers [2, 3] and provide additional prognostic information independent of clinicopathological features [4].ResultsData from all patients with ER+ Her2neu− breast cancer undergoing Oncotype DX® testing between 2011 and 2014 at a tertiary referral center in Germany were analyzed. Oncotype DX® was performed in 69 cases, in 2 cases data were missing and in 3 cases Oncotype DX® could not be performed by the company. The results showed a low risk in 39 cases, an intermediate risk in 22 cases and a high risk in 3 cases. Based on Oncotype results, treatment recommendations were changed in 39 of 64 patients (61%). Before Oncotype DX® testing, chemotherapy was recommended in 67 patients, afterwards only in 25 patients. Data from 44 of 67 patients were matched to controls for stage, tumor grade, menopausal and hormone receptor status. Within a mean observation time of 19.7 months, cancer recurrence was observed in two patients.ConclusionsOncotype DX® testing can be recommended for risk-tailored chemotherapy. Results should be validated in larger prospective studies.